IMPLEMENTATION OF BEACH BALL TYPE DISCUSSION LEARNING MODEL WITH MIND MAPPING STRATEGY TO TRAIN CREATIVE THINKING SKILL IN CLASS X ON CHEMICAL BOND MATTER (UNESA Journal of Chemical Education, 2019)
This study aimed to train students’ creative thinking skills through the implementation of beach ball type discussion learning model with mind mapping strategy in class X on chemical bond matter. The method of this research used pre-experimental with one group pretest posttest design. Instruments used observation sheets (implementation of learning activity and student activity), assessment sheets (mind map and pretest posttest), and questionnaire sheets (student responses). The implementation conducted in three meeting. Data analysis technique used quantitative and qualitative. The results of this research showed that: 1) the percentage result of the implementation beach ball type discussion learning model with mind mapping strategy for all aspects in every meeting was in very good category, 2) the dominant students’ activity in implementation beach ball type discussion learning model with mind mapping strategy at the first meeting, students paid attention to the teachers explanation of 39.23%, the second meetings, students had discussions of 26.59% and the third, students had discussions of 28.95%, 3) the creative thinking skill to create mind mapping had variation category, 79% in very creative (state 4) category and 21% in creative (state 3) category. Meanwhile in the task, they had in very creative category, 4) the learning outcome showed that the creativity increased 100% in concept (high category) and mind mapping 97% in high category meanwhile the other 3% in medium category, 5) good response from students with an average percentage of positive responses as 83.76% after implementation of beach ball type discussion learning model with mind mapping strategy. Keywords: Mind mapping, Beach Ball, Chemical Bond